PENGARUH KOMUNIKASI INTERN TERHADAP SEMANGAT KERJA PEGAWAI RUMAHSAKIT UMUM (RSUD) DR. H. CHASAN BOESOEIRIE TERNATE - Safri Basir (Program Studi Manajemen Fakultas Ekonomi dan Bisnis Universitas Khairun, 2015)
Abstract.This research aim to to know the influence of communications intern to spirit of officer jobby partial or visible individually at calculation result analyses the doubled linear regression, inferentialthat variable of communications intern have an effect on the significant to spirit of Public Hospitalofficer job] of Area ( RSUD) Dr. H. Chasan Boesoirie Ternate. Result of analysis of correlationcoefficient in this research, there are strong positive relation between communications intern hotlywork officer. This is visible from value of coefficient determinantnt (R2). Or can be told by there areinfluence of between variable of communications intern to spirit of Public Hospital officer job of Area( RSUD) Dr. H. Chasan Boesoirie Ternate.